Combined Therapy With Adipose‐Derived Mesenchymal Stem Cells and Ciprofloxacin Against Acute Urogenital Organ Damage in Rat Sepsis Syndrome Induced by Intrapelvic Injection of Cecal Bacteria. (13th April 2016) - Sung, Pei-Hsun; Chiang, Hsin-Ju; Chen, Chih-Hung; Chen, Yi-Ling; Huang, Tien-Hung; Zhen, Yen-Yi; Chang, Meng-Wei; Liu, Chu-Feng; Chung, Sheng-Ying; Chen, Yung-Lung; Chai, Han-Tan; Sun, Cheuk-Kwan; et al.
Abstract : Combined therapy with autologous adipose‐derived mesenchymal stem cells and ciprofloxacin was found to be superior to either therapy alone in improving the outcome in a rodent sepsis model. Abstract : We hypothesized that combined treatment with autologous adipose‐derived mesenchymal stem cell (ADMSC) and ciprofloxacin is superior to ciprofloxacin only in reducing sepsis‐induced urogenital organ damage and mortality in rat sepsis syndrome (SS) caused by intrapelvic injection of cecal bacteria (1.0 × 10 4 cells per milliliter; total, 5.0 ml). Male Sprague‐Dawley rats ( n = 60) equally divided into group 1 (sham‐control), group 2 (SS), group 3 (SS‐ADMSC [5.0 × 10 5 intravenously at 0.5, 6, and 18 hours after sepsis induction]), group 4 (SS‐ciprofloxacin [3.0 mg/kg, b.i.d.] for 5 days), and group 5 (SS‐ADMSC‐ciprofloxacin) were sacrificed by day 5. Mortality rate and creatinine level were highest in group 2 and lowest in group 1 and significantly higher in groups 3 and 4 than those in group 5, but there was no difference between groups 3 and 4 (all p < .005). The kidney injury score, inflammatory biomarker expressions at protein (tumor necrosis factor‐1α, nuclear factor‐κB, matrix metallopeptidase‐9, regulated on activation, normal T‐cell expressed and secreted, interleukin‐1β) and cellular (CD14+, migratory inhibitor factor positive, CD68+) levels in kidneys and urinary bladder were lowest in group 1 and highest in group 2, higher in group 4 than in groups 3 and 5, and higher in group 3 than in group 5 (all p < .001). Protein expressions of apoptosis (Bax, cleaved caspase 3 and poly[ADP‐ribose] polymerase 1, p21 protein [Cdc42/Rac]‐activated kinase 2) and oxidative stress (oxidized protein, NADPH oxidase (NOX)‐1, NOX‐2) in these organs showed an identical pattern compared with that of inflammation in all groups (all p < .001). In conclusion, ADMSC‐assisted ciprofloxacin therapy offered an additional benefit by reducing acute urogenital organ damage in rat. Significance: Autologous adipose‐derived mesenchymal stem cell‐assisted ciprofloxacin therapy offered an additional benefit by reducing acute urogenital organ damage in rats.